Aspartate aminotransferase as a biomarker in periodontal disease: A comparative in vitro study - Sabin Siddique; Ganesh Shenoy Panchmal; Fawaz Pullishery (Wolters Kluwer Medknow Publications, 2016)
Background: Estimation of biomarkers in saliva could offer an attractive opportunity for the diagnosis of periodontal diseases. The aim of this study was to investigate the aspartate aminotransferase (AST) levels in the saliva of patients with periodontal disease. Materials and Methods: Twenty patients were assigned to each of the three groups - C0, C3, and C4 based on their largest Community Periodontal Index of Treatment Needs (CPITN) code, totaling 60 participants. Immediately after a single mouth rinse with 15 mL of water to wash out exfoliated cells, about 1 mL of unstimulated saliva was collected in sterile plastic containers and transported to the biochemical laboratory for spectrophotometric analysis. Results: There were significant differences between levels of AST from the groups C0, C3, and C4. There was a significant positive correlation between clinical parameters and AST concentration in the saliva of each group. There was no statistical significance between males and females in all three groups. Conclusion: AST levels in the saliva increased with increase in the CPITN score. Group C0 had the least while group C4 had the highest AST level. High levels of AST are characteristic features of periodontitis affected subjects. Hence, monitoring the levels of AST in the saliva could be utilized as periodontal disease markers.